2011
DOI: 10.1007/s00441-011-1226-2
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of vascularized adipose constructs

Abstract: Adipose tissue engineering offers a promising alternative to the current surgical techniques for the treatment of soft tissue defects. It is a challenge to find the appropriate scaffold that not only represents a suitable environment for cells but also allows fabrication of customized tissue constructs, particularly in breast surgery. We investigated two different scaffolds for their potential use in adipose tissue regeneration. Sponge-like polyurethane scaffolds were prepared by mold casting with methylal as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
23
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 48 publications
1
23
0
2
Order By: Relevance
“…These findings are consistent with other studies considering in vivo tissue responses to PCL, where absent or minimal macrophage responses were reported within subcutaneous scaffolds over a 6-month period in rabbits [Lam et al, 2009] and in craniotomy defects in rats after 28 days [Byers et al, 2006]. Other studies in mice reported only mild inflammatory responses to PCL in a vessel loop model at 2 and 4 weeks [Wiggenhauser et al, 2012] and subcutaneously at 1 and 3 months [Seyednejad et al, 2012]. Only one study [Baker et al, 2011] characterised the macrophage response using immunohistochemistry, and in contrast to our findings in a similar rat model the presence of surface-adherent CD68+ macrophages was noted in porous PCL implants that had been chemically cross-linked.…”
Section: Discussionsupporting
confidence: 82%
“…These findings are consistent with other studies considering in vivo tissue responses to PCL, where absent or minimal macrophage responses were reported within subcutaneous scaffolds over a 6-month period in rabbits [Lam et al, 2009] and in craniotomy defects in rats after 28 days [Byers et al, 2006]. Other studies in mice reported only mild inflammatory responses to PCL in a vessel loop model at 2 and 4 weeks [Wiggenhauser et al, 2012] and subcutaneously at 1 and 3 months [Seyednejad et al, 2012]. Only one study [Baker et al, 2011] characterised the macrophage response using immunohistochemistry, and in contrast to our findings in a similar rat model the presence of surface-adherent CD68+ macrophages was noted in porous PCL implants that had been chemically cross-linked.…”
Section: Discussionsupporting
confidence: 82%
“…51 It has been shown that tissues engineered ex vivo based on scaffolds can become vascularized upon implantation into a host. 40 It was also reported that grafting of human ASC grown in spheroids is similarly followed by in vivo angiogenesis. 52 Interestingly, a recent study demonstrated that scaffold-free spheroids preserve multilineage potential of MSC.…”
Section: Discussionmentioning
confidence: 99%
“…39 More rigid, sponge-like scaffolds made from materials such as hydroxyapatite, or synthetic organic polymers casted using foaming agents, have also been introduced. 40,41 While artificial matrices are often used in tissue modeling, the relevance of tissue composition achieved with their help to in vivo settings has remained questionable. Recently, matrix scaffolds based on decellularized native tissues have gained popularity.…”
Section: Discussionmentioning
confidence: 99%
“…Cronin et al (2004) placed a split silicone tube around an arteriovenous pedicle in the mouse groin, thus inducing the formation of newly vascularized tissue. Wiggenhauser et al (2012) used the same mouse model as presented here to vascularize adipose tissue. Both Cronin et al Fig.…”
Section: Discussionmentioning
confidence: 99%